Subterranean Life-Style Does Not Limit Long Distance Dispersal in African Mole-Rats - Finn, Kyle T.; Thorley, Jack; Bensch, Hanna M.; Zöttl, Markus (Frontiers in Ecology and Evolution, 2022)
Dispersal from the natal site to breeding sites is a crucial phase in the life history of animals and can have profound effects on the reproductive ecology and the structure of animal societies. However, few studies have assessed dispersal dynamics in subterranean mammals and it is unknown whether dispersal distances are constrained by living underground. Here we show, in social, subterranean Damaraland mole-rats (Fukomys damarensis), that a subterranean lifestyle does not preclude long distance dispersal and that both sexes are capable of successfully dispersing long distances (> 4 km). Body condition did not predict dispersal distance, but dispersers from larger groups traveled farther than individuals from smaller groups. Subsequently we show in a phylogenetically controlled comparative analysis of dispersal distances in subterranean and surface-dwelling rodents that living underground does not constrain dispersal distances and that dispersal capacity is mainly a consequence of body size in both lifestyles.